2016
DOI: 10.1007/s00467-016-3327-3
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal patterns of urine biomarkers in infants across gestational ages

Abstract: Among healthy neonates, urinary biomarkers vary with GA. These data support the use of urinary biomarkers in the assessment of normal kidney development in the absence of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 37 publications
2
23
3
3
Order By: Relevance
“…A study by Chen et al reported that the median value of urine NGAL in third day of life in term infants was 88.1 ng/mL . Even higher urine NGAL levels on first day of life was published by DeFreitas et al, but the study only comprised 13 neonates . In contrast to our study, Sarafidis et al found much lower urine NGAL levels in a healthy reference group, which were 6.8 ng/mL (25–75% interquartiles 3.1–15.2 ng/mL), 7.1 ng/mL (2.7–17.7 ng/mL) and 1.1 ng/mL (0.9–1.9 ng/mL) on the first, third and tenth day of life, respectively .…”
Section: Table Of Demographics and Results According To Gendercontrasting
confidence: 92%
“…A study by Chen et al reported that the median value of urine NGAL in third day of life in term infants was 88.1 ng/mL . Even higher urine NGAL levels on first day of life was published by DeFreitas et al, but the study only comprised 13 neonates . In contrast to our study, Sarafidis et al found much lower urine NGAL levels in a healthy reference group, which were 6.8 ng/mL (25–75% interquartiles 3.1–15.2 ng/mL), 7.1 ng/mL (2.7–17.7 ng/mL) and 1.1 ng/mL (0.9–1.9 ng/mL) on the first, third and tenth day of life, respectively .…”
Section: Table Of Demographics and Results According To Gendercontrasting
confidence: 92%
“…No information on the PDA was given in that study [33]. Urinary albumin has been found to be increased in preterm neonates with asphyxia and respiratory distress and has been suggested as a possible biomarker of AKI in newborns [32, 34] and preterm neonates [35]. In concordance with our findings FENa is known to be very high in preterm neonates and inversely related to gestational age [36].…”
Section: Discussionsupporting
confidence: 86%
“…In a prospective study of 252 children who presented to the emergency department, urinary β 2 M, NGAL, and KIM-1 demonstrated good accuracy (AUC > 0.7–0.8) in predicting AKI (192). The caveat with using β 2 M as a biomarker for AKI is that the level varies with gestational age, hence caution will need to be exercised in using this serum marker in premature infants (193, 194). …”
Section: Urinary β2m For the Assessment Of Tubular Functionmentioning
confidence: 99%